2018
DOI: 10.1017/9781108560672
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Decision

Abstract: The concept of organization took on clearer contours only in the second half of the nineteenth century. In the Middle Ages there had been no need for a special concept for what we now call organizations. It would have lacked substance: the stratification of family households and corporations provided for social order, which for the rest was subject to a multiplicity of legal arrangements. 1 Only in the nineteenth century did it become usual to conceptualize the organization as a social formation distinct from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
201
0
13

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 164 publications
(214 citation statements)
references
References 4 publications
0
201
0
13
Order By: Relevance
“…This is true also for modern systems theory as developed by Luhmann (2012, 2013) (see, e.g., Andersen & Born, 2008; Kette & Tacke, 2015; Kühl, 2015; Nassehi, 2005; Schirmer & Michailakis, 2015). Although defining organizations as processual entities consisting of decision communications, Luhmann insisted that organizations need to preselect certain persons as members in an appointment procedure thereby distributing rights to participate in the organizational communication processes (Luhmann, 2018, p. 45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true also for modern systems theory as developed by Luhmann (2012, 2013) (see, e.g., Andersen & Born, 2008; Kette & Tacke, 2015; Kühl, 2015; Nassehi, 2005; Schirmer & Michailakis, 2015). Although defining organizations as processual entities consisting of decision communications, Luhmann insisted that organizations need to preselect certain persons as members in an appointment procedure thereby distributing rights to participate in the organizational communication processes (Luhmann, 2018, p. 45).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, most scholars—including Luhmann—see membership as a structural element or a fixed premise implying that certain individuals become members at one point and then remain members until their memberships are terminated. In this rather static view, membership is tightly coupled to certain identifiable persons who are the members (see, e.g., Ahrne, 1994; Aldrich, 2008; Andersen & Pors, 2014; Drori, Meyer, & Hwang, 2006; King et al, 2010; Luhmann, 2018). Some literature, on the other hand, has suggested that membership should be seen as a precarious process in which the degree of belonging to an organization is constantly renegotiated.…”
Section: Introductionmentioning
confidence: 99%
“…She examines more closely in what forms volunteers are addressed as members within three different partnership projects in the very same municipality. In her work, a crucial aspect of membership is under pressure: namely, the assertion that members become members through their obligations to accept the decisions of the organization (Luhmann, 1964, 2018). When it comes to volunteers, these do not have contractual obligations to the organization.…”
Section: An Overview Of the Special Issuementioning
confidence: 99%
“…Organizations, hence, are now understood as a specific kind of social system, that is, a system mainly concerned with making decisions. Accordingly, Luhmann (2018) defines the structures of an organization no longer in terms of formal/informal but as premises for decision‐making: for example, in the form of personnel recruitment, communication channels, hierarchies, rules and culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation